Implementation and performance barriers in Iran’s breast cancer screening program: a qualitative case study - Jabbari, Arezoo; Najafpour, Zhila; Ourang, Sima; Loveimi, Somayeh; Bohrani, Reyhane; Baymani, Mahsa (Frontiers in Public Health, 2025)
IntroductionCancer screening programs (CSPs) are essential for early detection and improving survival rates; however, they often encounter barriers to effective implementation. This study aims to identify the key challenges faced in implementing the Breast Cancer Screening Program (BCSP) in Iran, with the goal of providing insights to enhance the program’s effectiveness and accessibility.MethodsThis study was conducted as an observational and qualitative research to assess the implementation status and identify barriers within the Breast Cancer Screening Program (BCSP). Data were collected through a combination of interviews, process observations, and document reviews. A purposive sample of 37 participants was interviewed, including individuals involved in the management, implementation, or evaluation of the screening program. Thematic content analysis was employed to analyze the data, with saturation achieved to ensure comprehensive coverage of the study’s objectives.ResultsThe study identified several key barriers to the effective implementation of breast cancer screening programs, which were categorized into three main dimensions: infrastructural, managerial, and healthcare service delivery. The most critical issues in infrastructural category were a lack of trained healthcare personnel, insufficient screening facilities, inaccurate registration systems, fragmented databases, and poor data quality control. Key barriers in the managerial dimension include the absence of a mechanism for identifying and inviting women eligible for cancer screening, as well as inadequate monitoring of non-responders to follow-up. Overcrowding during peak times, long waiting periods, inaccurate triage, and lack of general practitioners (GPs) at the primary level of public healthcare were the identified barriers in service delivery in cancer screening. Additionally, interviews with women revealed several barriers, such as low perceived risk, fear and anxiety, lack of family support, and cultural or religious objections, all of which further hindered participation in breast cancer screening.ConclusionThis study highlights the critical barriers to the implementation of breast cancer screening programs in Iran, most of which appear to stem from systemic failures. Addressing these challenges requires a comprehensive, strategic approach that targets the identified obstacles at multiple levels. Overcoming these barriers is crucial to improving the accessibility, efficiency, and overall effectiveness of breast cancer screening programs, ultimately enhancing early detection and patient outcomes.